ADVERSE DRUG REACTIONS IN PEDIATRIC PATIENTS IN A TERTIARY CARE HOSPITAL IN KOLLAM - R, REEJA; JS, BEENA; AS, AJITHKRISHNAN; NAIR R, BINDULATHA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Adverse drug reactions have not been as thoroughly studied in children as they have in adults. Extrapolation of efficacy, dosing regimens, and ADRs from adult data are inappropriate owing to developmental changes in physiology and drug handling. There is a lack of local data regarding the potential risk of ADRs in pediatric patients. Objective of this study is to identify the adverse drug reaction (ADR) profile in pediatric patients. Methods: In this cross-sectional study, 450 children attending the pediatric inpatient and outpatient department were selected, and the CDSCO reporting form for suspected ADR reporting forms was collected from those who had any adverse events by the consulting pediatrician. Later, this form was analyzed for the details for ADRs and assessed for causality, severity, and preventability using Naranjo’s algorithm, Hartwig and Siegel scale, and modified Schumock and Thornton scale of adverse drug reactions. Results: The cross-sectional study revealed a prevalence of 12.89%. Antibiotics caused more ADRs than any other group of drugs. Dermatological ADRs were the most common. Most ADRs were not preventable and were of moderate severity. The causality assessment showed that most ADRs were possible category. Conclusion: The ADRs are often unrecognized. We need more strict monitoring for early detection, treatment, and more importantly prevention of these events in the future. For that, more awareness programs, CMEs and teamwork are extremely important among the caregivers.